Studi pharmacovigilance obat di puskesmas X Yogyakarta - mustika muthaharah; Dyah Aryani Perwitasari; Nyoman Kertia (Universitas Ahmad Dahlan, 2017)
ABSTRACTÂ The increasingÂ use of herbal medicine in community also increase adverse event and toxicity report. Adverse events and toxicity can be detected with pharmacovigilance system. Adverse Drug Reaction (ADR) of herbal medicines are rarely studied in Indonesia. With the increasing use of herbal medicines in Indonesia, pharmacovigilance studies are necessary to detect the incidence of ADR. The purpose of this study is to describe the incidence of ADR on the use of herbal medicines. This research is a descriptive study using retrospective data. Research was conducted for 3 months by taking 10-month retrospective data backward using medical record. Interviews were conducted to identify the occurrence of ADR and assessment of quality of life using Naranjo algorithm.The result showed that three (13.63%) of 22 patients experiencing the ADR with probability of probable categories (1) and possible (2). The symptom of ADR that showed was the increased frequency of defecation, decreased in stool consistence and diuresis.The results of this study concluded that there are ADR event in patients who have been prescribed herbal medicine in Public Health Center X Yogyakarta.Â Keywords: ADR, herbal medicine, pharmacovigilance.